(untitled) (European Journal of Pure and Applied Mathematics, 2010)
In this paper, we introduce and investigate a new class of sets and maps between topological spaces called supra bâˆ’open sets and supra bâˆ’continuous maps, respectively. Furthermore, we introduce the concepts of supra b-open maps and supra b-closed maps and investigate several properties of them.